2017
DOI: 10.1371/journal.pone.0173062
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of fecal microbial communities in cattle and Bactrian camels

Abstract: Bactrian camels may have a unique gastrointestinal (GI) microbiome because of their distinctive digestive systems, unique eating habits and extreme living conditions. However, understanding of the microbial communities in the Bactrian camel GI tract is still limited. In this study, microbial communities were investigated by comparative analyses of 16S rRNA hypervariable region V4 sequences of fecal bacteria sampled from 94 animals in four population groups: Inner Mongolian cattle (IMG-Cattle), Inner Mongolian … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 21 publications
2
16
0
1
Order By: Relevance
“…The taxonomic assignment revealed that most of predicted genes were assigned to the Bacteroidetes/Chlorobi group. This corroborates results of the bacterial diversity analysis of the dromedary fecal microbiota, based on analyzing the 16s rRNA gene previously reported [ 4 , 6 , 24 ] demonstrating that camel rumen metagenome is dominated by Bacteroidetes and Firmicutes. This denote that, as is other herbivores, bacteria related to those phyla are the predominant fiber degraders in rumen microbiota, producing a large number of plant cell wall degrading enzymes [ 25 , 26 ].…”
Section: Discussionsupporting
confidence: 92%
“…The taxonomic assignment revealed that most of predicted genes were assigned to the Bacteroidetes/Chlorobi group. This corroborates results of the bacterial diversity analysis of the dromedary fecal microbiota, based on analyzing the 16s rRNA gene previously reported [ 4 , 6 , 24 ] demonstrating that camel rumen metagenome is dominated by Bacteroidetes and Firmicutes. This denote that, as is other herbivores, bacteria related to those phyla are the predominant fiber degraders in rumen microbiota, producing a large number of plant cell wall degrading enzymes [ 25 , 26 ].…”
Section: Discussionsupporting
confidence: 92%
“…Bactrian camels inhabit areas with arid, cold climates (long, cold winters and short summers) in Mongolia. These areas have scarce water sources and sparse vegetation, and the diets of camels in these regions are relatively simple [36]. At present, Mongolian camels have not been identified, apart from one breed.…”
Section: Resultsmentioning
confidence: 99%
“…Another phyla Deinococcus-Thermus decomposed high-molecular-weight organic matter such as starch, cellulose, proteins, xylan, and chitin [22].…”
Section: Discussionmentioning
confidence: 99%